Management of anticoagulant and antiplatelet therapy in patients undergoing interventional pulmonary procedures - Vikas Pathak; J. Erin Allender; Mollie W. Grant (European Respiratory Review, 2017)
There has been great progress in antithrombotic therapy over the past several years. Its use has increased with the advent of novel anticoagulants, as these medications do not require frequent blood tests for monitoring. Antithrombotic therapy is aimed at reducing the risk of thromboembolic events in patients with atrial fibrillation, coronary artery disease, deep vein thrombosis, valvular heart disease and pulmonary embolism. These patients are often critically ill and frequently undergo urgent interventions requiring discontinuation of anticoagulant or antiplatelet therapy which can increase the risk of thrombosis; however, continuing these agents can lead to increased risk of haemorrhage. The purpose of this article is to summarise the literature surrounding the safety of using antiplatelet and anticoagulant therapies in patients undergoing interventional pulmonary procedures.